2004
DOI: 10.1158/1078-0432.ccr-03-0130
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen Messenger RNA Expression Using Nested Reverse Transcription-PCR in the Peripheral Blood During Follow-up Period of Patients Who Underwent Curative Surgery for Biliary-Pancreatic Cancer

Abstract: Purpose: Outcome for patients with biliary-pancreatic cancer is still poor, despite curative operation. We investigated the clinical significance of molecular detection of circulating cancer cells in the blood as an early indicator of relapse during follow-up of patients who underwent a curative operation for biliary-pancreatic cancer.Patients and Methods: We followed 53 patients who underwent a curative operation for biliary-pancreatic cancer between 1996 and 2001. We used reverse transcription-PCR in the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 23 publications
(12 reference statements)
1
39
0
Order By: Relevance
“…Mataki et al (33) reported the longitudinal analysis of CEA mRNA expression and two tumor markers, serum CEA and serum carbohydrate antigen 19-9, and found that CEA mRNA was expressed in two recurrent cases without tumor marker Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…Mataki et al (33) reported the longitudinal analysis of CEA mRNA expression and two tumor markers, serum CEA and serum carbohydrate antigen 19-9, and found that CEA mRNA was expressed in two recurrent cases without tumor marker Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…(12,13) The RT-PCR is a useful assay for detecting circulating tumor cells (CTC) within blood specimens from patients with various malignancies, including gastric cancer. (14)(15)(16)(17)(18) We reported that the presence of CTC correlates with tumor progression and outcomes of patients with esophageal, gastric and biliary-pancreatic cancer.…”
mentioning
confidence: 99%
“…(12,13) The RT-PCR is a useful assay for detecting circulating tumor cells (CTC) within blood specimens from patients with various malignancies, including gastric cancer. (14)(15)(16)(17)(18) We reported that the presence of CTC correlates with tumor progression and outcomes of patients with esophageal, gastric and biliary-pancreatic cancer. (14)(15)(16)(17)(18) Several epithelial-specific antigens such as CEA, cytokeratin-19, and cytokeratin-20, have been used generally in many studies of CTC detection in gastric cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These included immunocytochemistry with the use of antibodies for different tumour markers, although they are not tumourspecific (7). In conjunction with the antibody staining techniques, reverse transcriptase polymerase chain reaction (RT-PCR) was introduced as a powerful method for further analysis of potentially micrometastasizing tumour cells (8)(9)(10)(11)(12). This highly sensitive technique was designed for the detection of mRNA of presumptive tumour markers (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%